Rate effects of cylindrical cavity expansion in fine-grained soil - Cheng Chen; Yong Wang; Zhonghua Sun; Xun Wu; Xiaowei Geng; Xianwei Zhang (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
Soil responds to cavity expansion is inherently rate-dependent, especially in the case of fine-grained soils. To better understand such rate effects, self-boring pressuremeter tests were conducted on Kunming peaty soil within a strain rate range of 0.1%/min to 5.0%/min. The results showed a clear dependence of cavity pressure and excess pore pressure (EPP) on strain rates—both increased with higher rates for a given radial displacement. In light of the experimental results, three cases of cylindrical cavity expansion were investigated using the finite element method and analytical method, partially drained expansion in Modified Cam-Clay (MCC) soil, and undrained and partially drained expansion in elastoviscoplastic (EVP) soil. The EVP behavior was and modeled using the MCC model and the overstress viscoplastic theory. The results indicated that over the strain rate range of 0.0001%/min and 50%/min, the rate response of cavity pressure for the case of partially drained expansion in MCC soil (permeability coefficient ranging from 5 × 10−6 m/s to 2.5 × 10−11 m/s) is not obvious, while the EPP response during undrained expansion in EVP soil shows rate-independent. Only the partially drained solution for cavity expansion in EVP soil captured the rate-sensitive responses of both cavity pressure and EPP, confirmed by the pressuremeter tests on the Kunming peaty soil, Saint-Herblain clay, and Burswood clay. This suggests that the rate effect results from a combination of drainage-related and time-dependent soil behavior. Parametric studies further demonstrated that both viscous behavior and the overconsolidation ratio significantly influence cylindrical cavity expansion response, and the drainage conditions during expansion can be assessed using a nondimensional velocity.